Emissions reduction by using e-components in 48 V mild hybrid trucks under dual-mode dual-fuel combustion. (1st October 2021) - García, Antonio; Monsalve-Serrano, Javier; Martinez-Boggio, Santiago; Gaillard, Patrick
Highlights: Evaluation of an electrical turbocharger and exhaust gas recirculation pump benefits. Optimum configuration selected by means of an engine modeling approach. Homologation and real driving conditions considered for the results analysis. The use of both e-components allows improving the fuel consumption between 2% and 17% Abstract: The European community foresees a 15% CO2 tailpipe emissions restriction in 2025 and 30% in 2030 for the trucks. While battery electric vehicles would help to reach these levels, their low ranges make them unfeasible for the good transport sector. By this reason, hybrid vehicles are considered the bridge between the current technology and the battery electric vehicles. The 48 V mild hybrid technology is an effective solution due to its low cost and changes needed with respect to the current technology. It also allows the use of electrical components that help to improve the brake thermal efficiency, reduce the emissions and recover energy. This works explores the potential of an electric turbo compound (e-TC) and an electric exhaust gas recirculation pump (e-EGR pump) in a mild hybrid truck platform working under dual-mode dual-fuel (DMDF) combustion with diesel and gasoline. The e-components are simulated by means of 0D-Engine modeling. Finally, a general overview of the potential in real applications is done by means of a vehicle model considering different driving cycles and truck payloads for two truck platforms (18-ton and 25-ton maximum payload). The results show that to achieve the large EGR rates required by the DMDF combustion and meet the air requirements, it necessary the use of both e-components together. The evaluation at vehicle conditions allows to conclude that the mild hybrid platform allows to reduce the CO2 emissions around 6% in homologation conditions and 10% in urban cycles. Moreover, it was found that the use of e-components only improves the vehicle efficiency in the cases with low truck payloads.